Influence of Air Vents Management on Trombe Wall Temperature Fluctuations: An Experimental Analysis under Real Climate Conditions - Ana Briga-Sá; Anabela Paiva; João-Carlos Lanzinha; José Boaventura-Cunha; Luís Fernandes (Energies, 2021)
The Trombe wall is a passive solar system that can improve buildings energy efficiency. Despite the studies already developed in this field, more research is needed to assess the possibility of its integration in buildings avoiding user intervention. In this study, the influence of air vent management and materials’ heat storage capacity upon its thermal performance, particularly in the temperature fluctuation and indoor conditions, was discussed. Comparing two days with similar solar radiation (SR) for non-ventilated (NVTW) and ventilated (VTW) Trombe walls, a differential of 43 °C between the external surface temperature and the one in the middle of the massive wall was verified for NVTW, while for VTW this value was 27 °C, reflecting the heat transfer by air convection, which reduced greenhouse effect, solar absorption and heat storage. A cooling capacity greater than 50% was verified for VTW compared to NVTW during night periods. An algorithm for the Trombe wall’s automation and control was proposed considering SR as variable. Air vents and external shading devices should be open when SR exceeds 100 W/m2 and closed for 50 W/m2 to obtain at least 20 °C inside the room. Closing for 50 W/m2 and opening for values lower that 20 W/m2 is suggested for summer periods.